2014
DOI: 10.1088/1742-6596/551/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Spin-polaron band in the ferromagnetic heavy-fermion superconductor UGe2

Abstract: In strongly correlated materials, cooperative behaviour of the electrons causes a variety of quantum ordered states that may, in some cases, coexist 1-3 . It has long been believed, however, that such coexistence among ferromagnetic ordering, superconductivity and heavy-fermion behaviour is impossible, as the first supports parallel spin alignment while the conventional understanding of the latter two phenomena assumes spin-singlet or antiparallel spins. This understanding has recently been challenged by an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 108 publications
(380 reference statements)
0
3
0
Order By: Relevance
“…UGe 2 also indicate small magnetic moment compared to the full moment of U 5f electron, 3.6 μ B /U. This is due to the large magnetic anisotropy, due to the spin polarization band [58][59][60]. The magnetic anisotropy energy is estimated as 6.17 meV = 107 T [58].…”
Section: Sample λ (Kj/kg) δS (J/kg K) δT M (K) T M (K) δT Ad (μ 0 H[t]) (K) Referencementioning
confidence: 95%
“…UGe 2 also indicate small magnetic moment compared to the full moment of U 5f electron, 3.6 μ B /U. This is due to the large magnetic anisotropy, due to the spin polarization band [58][59][60]. The magnetic anisotropy energy is estimated as 6.17 meV = 107 T [58].…”
Section: Sample λ (Kj/kg) δS (J/kg K) δT M (K) T M (K) δT Ad (μ 0 H[t]) (K) Referencementioning
confidence: 95%
“…A recent report has shown that bac-14 stabilizes the Au surface through-space by anion and cation interactions (Fig. 46 Aqueous suspensions of Au/bac-14 NPs were found to scavenge electrons at unprecedented rates, k e = 5 × 10 14 M −1 s −1 at μM concentrations. 44 In the present work, to determine the rate of electron capture by AuNP/bac-14 in solution as a function of temperature, positive anti-muons (µ + ) 45 were used as spin probes as well as the ionizing radiation.…”
Section: Resultsmentioning
confidence: 96%
“…in a slurry made by adding small amount of water to AuNP solid) it is possible that muons would cause radiation damage to the AuNPs during radiolysis process. 46 Aqueous suspensions of Au/bac-14 NPs were found to scavenge electrons at unprecedented rates, k e = 5 × 10 14 M −1 s −1 at μM concentrations. The rate constant reported here is considerably larger than rate constants of reactions involving equilibrated solvated electrons in water, suggesting ET to AuNPs occurs at a rate that competes with the solvation of the ionized electron ("dry electron"/non-equilibrium electrons before solvation).…”
Section: Resultsmentioning
confidence: 98%